Live long and evolve : what Star Trek can teach us about evolution, genetics, and life on other worlds - Noor, Mohamed A. F. (Princeton University Press, 2018)
An engaging journey into the biological principles underpinning a beloved science-fiction franchiseIn Star Trek, crew members travel to unusual planets, meet diverse beings, and encounter unique civilizations. Throughout these remarkable space adventures, does Star Trek reflect biology and evolution as we know it? What can the science in the science fiction of Star Trek teach us? In Live Long and Evolve, biologist and die-hard Trekkie Mohamed Noor takes readers on a fun, fact-filled scientific journey.Noor offers Trekkies, science-fiction fans, and anyone curious about how life works a cosmic gateway into introductory biology, including the definitions and origins of life, DNA, reproduction, and evolutionary processes, such as natural selection and genetic drift. For instance, he shows how the rapid change in a population of nanite robots follows basic principles of natural selection that apply to species on Earth. He explains how certain creatures depicted in the series are bisexual, not asexual, and what evolutionary advantage that difference provides. And he considers factors that affect successful interspecies mating and delves into what keeps species distinct. Noor discusses the importance of research and how Star Trek has influenced scientists to engage in cutting-edge work.Giving readers irresistible and entertaining insights, Live Long and Evolve looks at some of the powerful science behind one of the most popular and longest-running science-fiction series.